Activities of Apiaceae essential oils and volatile compounds on hatchability, development, reproduction and nutrition of Pseudaletia unipuncta (Lepidoptera: Noctuidae) - Sousa, Rose Marie O. F. (2015)
The inhibitory activities of Anethum graveolens, Cuminurn cyminum, Foeniculum vulgare and Petroselinum crispum Essential Oils (EOs), plus eleven volatile compounds, on embryonic development of a phytophagous pest, Pseudaletia unipuncta (Lepidoptera: Noctuidae) were evaluated. Lethal and sub-lethal effects of some treatments during the postembryonic development were also monitored. The higher effectiveness to inhibit eggs hatching was achieved with P. crispum fruit EO and its two main compounds (apiole and myristicin). F. vulgare EOs, as well as the bioactive compound azadirachtin (1 mg mL(-1)) and the volatiles trans-anethole, estragole, (+)-fenchone, alpha-pinenes, (-)-beta-pinene and gamma-terpinene (15 mg mL(-1)), had negligible inhibitory effects on larvae emergence, although, some induced post-exposure mortality during larval phase. A. graveolens EO from leaves and stems, and six compounds, including azadirachtin, extended significantly the duration of larval development from 1.9 to 6.5 days. (+)-Fenchone and (-)-beta-pinene reduced significantly the oviposition potential of females, by 46% and 33%, respectively.Additionally, a quantitative nutritional approach was conducted in order to assess adverse effects of EOs and compounds on 4th instar larvae growth and metabolism. After 72 h of feeding with treated corn leaves (0.7 mg/leaf), P. crispum fruit EO (Pc-F) and azadirachtin (0.04 mg/leaf) caused significant adverse effects on larva nutrition (lower consumption and Relative Consumption Rate) and growth (weight loss and negative Relative Growth Rate), followed by trans-anethole and cuminaldehyde. As verified for the positive control azadirachtin, trans-anethole and cuminaldehyde had negative and significant influences on the Relative Metabolic Rate (RMR) and on the efficiency of conversion of food to biomass (measured as ECI and ECD), with consequent higher Metabolic Costs (MC) to the larvae.P. crispum EO from fruits revealed great potential as a controlling agent of P. unipuncta in early life stages, actin